The Twelve Jays of Christmas - Andrews, Donna (Andrews, Donna. Meg Langslow mysteries., 2022)
"The cast of Donna Andrews' New York Times bestselling Meg Langslow mystery series is back for an unforgettable holiday story in The Twelve Jays of Christmas. Meg's brother Rob and his fiancé Delaney have been engaged for some time now. In fear of their mothers' propensity for over-the-top celebrations, they decide to throw a party just before Christmas and then elope. When a blizzard traps their guests inside, the two mothers find out about the planned elopement and start trying to pull together the kind of over-the-top event the couple was trying to avoid in the first place. To make matters worse, a murder is afoot. Will Meg manage to help the snowbound would-be eloping couple thwart their mothers' grandiose wedding plans AND solve a murder among the assembled friends and relatives?"--